Propuesta de un manual de funciones, valuación de puestos por puntos y reglamento de admisión y empleo para la comercializadora herrera Román de la ciudad de Loja - Mogrovejo Salcedo, Maria Fernanda (2016)
Once the preparation of this thesis is complete, it is very important to put knowledge the main results were obtained throughout the investigation process, which may be summarized as follows: This research project had as its overall objective to make a "PROPOSAL FOR A MANUAL FUNCTIONS, VALUATION OF POSITIONS FOR POINTS AND REGULATION OF ADMISSION AND EMPLOYMENT FOR THE COMERCIALIZADORA HERRERA ROMAN CITY OF LOJA" the same that would assist with human talent of the company in various aspects such as performance of the functions of each position, appropriate recruitment techniques, fair and in accordance allocation of wages and finally a correct evaluation of staff performance and likewise had several objectives specific in which the development of this research is based, by the same as the problem being experienced by the company is determined. The company Comercializadora "Herrera Roman" located in the city of Loja, is recognized for its leadership in the development and marketing and distribution of food, meat products in general, canned, processed products as well as consumer. The methodology used for this research project is summarized in the use of the following methods: Inductive Method Deductive Method, Analytical Method, synthetic method and scientific method; Likewise use of some research techniques such as occurred: The Direct Observation, Interview and Survey, same as they be used to find and verify with certainty the problems being experienced by the company and the methodology used was begun analyze each one of you collected data. Among the main areas where found divided this research are: In the first instance the Proposed Functions Manual is the same as in its content describes the ideal profile for each of the posts taking into account: the identification of the position, the nature of the position, typical roles, responsibilities and skills, minimum requirements, working conditions, required for each job profile. In the second instance concerning the valuation of positions due to the dissatisfaction of employees in their salaries, the system of job evaluation was applied on points with their respective stages being fixed points for grades such as: Education, Experience Initiative , Liability per person, Liability Team, physical effort, mental effort, risks and establishing the appropriate score to each of the offices of the company which gave us Manager 300, Chief Financial Officer 250, Supervisor Portfolio 240, Assistant Portfolio 210, 250 Accountant, Accounting Assistant 170, 180 Biller, Head of Sales 220 210 Bodega Head, Bodega 160 Assistant, Vendor 150, 200 Chauffeur, Assistant cast 130; once the weight assigned to each of the positions a sum in which the following results were obtained was made: total points based on the valuation is 2670, while the total wages paid to employees is 7,777, 00 with these data the equation of the straight line which gave us as a result 3.07 based on the above-mentioned wage adjustment value with a value of 2.91 valuation in order to determine new salaries was done was applied.It is noteworthy that this revaluation is made only charges that were below the salary line in total amounted to 9 and are: Seller, Assistant Bodega, Biller, Assistant Portfolio Accounting Assistant, Chief Winery, Driver, Sales Manager and chief Financial Officer. And to end with the proposal after analyzing the staff working in the company has entered the same family or recommendations without the experience and knowledge needed for each of the posts; Recruitment, Selection, Recruitment, Induction them that are divided into chapters and articles according to the Law requested the same as they bring and allow the company: a regulation Admission and Employment the same consisting of four phases that are performed select the most appropriate staff for different posts required now or in the future. These being the most important conclusions that the staff of the company Comercializadora "Herrera Roman" can be said: The company does not have a manual of functions that expose and clarify the tasks to be performed in each of the positions, which generates disinformation when perform in it. It was also known that there are employees who do not have the profile indicated for the position they play within the company. According to the percentage of employees who are not satisfied with their salary a valuation of positions in which it was noted that a large number of positions require a reassessment in order to increase productivity and efficiency of employees was conducted. The structural organization of the company is not well organized, which causes confusion among employees, ignoring their dependencies and likewise it was concluded that when choosing the company personnel not done through a technical process